School Leader Preparation in the U.S. State of Virginia: Exploring the Relationship between Data Use in Standards and Program Delivery - Coby V. Meyers; Lisa Abrams; Tonya R. Moon; Michelle Hock (MDPI AG, 2024)
National school leadership standards are now de facto curriculum for preparation programs. Data use is embedded throughout standards to guide school improvement and classroom instruction. Yet, across a number of areas, pre-service principals do not appear ready to lead once in the field. Principals are responsible for using various data to guide internal policies, school cultures, and capacity building, largely supporting teachers by establishing norms, expectations, and clear visions for data use in instructional decisions. In this study, we examined leadership preparation programs in one U.S. state to understand how data use is addressed in leader preparation. Our analysis of course description, syllabi, and program director interview data resulted in the following findings: (1) programs and courses seldom explicitly acknowledged data use as a topic; (2) when data use was acknowledged as a topic, it was infrequently tied to standards; (3) connections between data use and instructional change were limited; and (4) most programs relied on internships for leadership preparation programs to learn data use practices. There are opportunities for programs to make connections between standards, data use, and instructional improvement more explicit, as well as to clarify expectations for and increase oversight of field-based mentors.